Narratives of fathering young children in Britain: linking quantitative and qualitative analyses. Issue 1 (1st January 2018) - Elliott, Heather; Parsons, Sam; Brannen, Julia; Elliott, Jane; Phoenix, Ann
ABSTRACT: The paper examines how in Britain the time fathers and couples spend in employment shifts in the first years of children's lives, the conditions under which this happens and how fathers feel about and experience time with their families and time in paid work. In order to achieve these aims new longitudinal analysis of the UK Millennium Cohort Study (MCS) is carried out together with secondary analysis of narrative case studies drawn from a qualitative study of Fatherhood across the Generations. By linking these datasets the paper examines the potential for corroboration and complementarity between different types of data. Further, it seeks to show how qualitative cases corroborate, elaborate and expand on the main employment trajectories in the MCS population of fathers and how these extend understandings of fathers' experience of time within families.